Two degrees of freedom flow-induced vibration and heat transfer of an isothermal cylinder. (June 2020) - Yang, Zuomei; Ding, Lin; Zhang, Li; Yang, Lin; He, Haoyu
Highlights: Displacement and surface-averaged Nu change periodically for cylinder in 2DOF FIV. Cylinder reaches max-amplitude as vortex streets transit from one row to two rows. Position of maximum local Nu moves periodically along the surface of FIV cylinder. The averaged Nu of 2DOF FIV cylinder increases by 5.73% than stationary cylinder at U* =6. Abstract: The effect of two-degree-of-freedom (2DOF) flow-induced vibration (FIV) on the characteristics of forced convective heat transfer from an isothermal circular cylinder is numerically simulated by commercial software-FLUENT in combination with the User Defined Function. The Reynolds number is 100, the flow is assumed to be two-dimensional, incompressible, and laminar. The undamped oscillator model is used to model the 2DOF FIV of the cylinder. The influence of reduced velocity on vortex formation, vibration response, and Nusselt number are discussed. The range of reduced velocity is 3 ≤  U* ≤10, where U*=U∞ / ( fn D ). The change of the reduced velocity has influence on the formation and shedding of the vortices, consequently, the vibration response and heat transfer of the cylinder are affected. Results show that the 2S (Single) vortex patterns and typical "figure-eight" shape trajectories can be observed at the studied reduced velocities. The displacement and surface-averaged Nusselt numbers vary periodically with time for the cylinder in FIV. Due to the vibration of cylinder, the position corresponding to the maximum local Nusselt number deviates from the front stagnation point. The best heat transfer performance is observed at U* =6 for cylinder in 2DOF FIV, and the time-space averaged Nusselt number is increased by 5.73% and 2.46% compared with the flow around a stationary cylinder and one degree of freedom FIV cylinder, respectively.